Typhonium morangense (Araceae), a new species from the tropical forest of Eastern Nepal - Rijan Ojha; Sudeep Rai; Harald Schneider (PhytoKeys)
A new species of the aroid genus Typhonium Schott has been discovered in Eastern Nepal. This species, named Typhonium morangense R.Ojha & S.Rai, is described based on comparative morphological examinations with closely related species from the Indian subcontinent. The new species is currently known only from Pathari Shanishchare Municipality in the Morang district of Eastern Nepal. It is the second species of Typhonium observed in Nepal, and the only one endemic to the country. A detailed description, color plate, geographic distribution, phenology, and morphological comparison of the new species with morphologically close species are provided. Given its restricted range and the low number of individuals observed in the wild, this species requires special attention from conservation biologists working in Eastern Nepal.